PENGARUH PENGGUNAAN TEKNOLOGI ALAT BERAT TERHADAP PRODUKTIFITAS KEGIATAN PERTAMBANGAN, STUDI KASUS PADA PERTAMBANGAN PASIR PT BALANGAN CITRA MANDIRI - Triyono, Triyono (KURVATEK, 2022)
Company productivity can be realized through the use of heavy equipment technology. Research conducted at PT. BCM located in Sleman, which is engaged in sand mining in the Kulonprogo region. Based on the results of interviews with company owners and company staff, PT.BCM currently still has two mining models, so it is possible to increase it. The purpose of the research conducted was to determine the difference in production effectiveness, between the traditional mining model and the mining model using heavy equipment, in order to increase company profits. The research method used is descriptive analysis. The results obtained based on interviews with the owners and employees of PT. BCM, as outlined in the table and comparative analysis. The results of the analysis can be used to assist management in making strategies to increase production results, so that the company's profits will increase Keywords: Effectiveness; Profit; Heavy equipment; Productivity